Aetiology and Clinical Profile of Acute Pancreatitis in a Tertiary Care Hospital - Hossain , Md Delwar; Mazumder , Nihar Ranjan; Hossain , Md Solaiman; Hassan , Md Nazmoul; Rabbi , Ahmed Noor E; Akter , Sabina; Hasan , SM Ali (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Acute Pancreatitis is a potentially serious condition with an overall mortality of 10%. Early diagnosis is important for its management. So clinician must carefully evaluate the patient with history, physical examination, laboratory tests and imaging studies before arriving a correct diagnosis. Death is more likely in certain subgroups of patients including elderly, co-morbidity, severe coexisting hospital acquired infection and organ dysfunction. Objectives: To assess aetiology and clinical profile of acute pancreatitis in a tertiary care hospital. Methods: A six-month Cross sectional study carried out at the department of Medicine, Comilla Medical College. Ethical approval from the institutional review board was obtained to ensure patient privacy and confidentiality. Results: The majority of patients are within the age group of 21-60 years (88.4%), with a higher proportion of males (71.2%) than females (28.8%). The most common clinical presentations were abdominal pain (95.6%) and nausea/vomiting (89.6%). Idiopathic (38%) and gallstone-related (38.4%) causes were the most common etiologies, while necrotizing pancreatitis (9.6%) and pancreatic pseudocysts (4.8%) were the most frequent complications. Regarding outcomes, a majority of patients experienced a favorable prognosis, with 64.4% recovering and being discharged. However, the complexity and severity of some cases were evident, as 17.6% of patients required referral to higher levels of care for further management. Additionally, a small percentage of patients left against medical advice (14.8%), and mortality was observed in 3.2% of cases. Laboratory investigations played a crucial role in diagnosing acute pancreatitis, and elevated levels of serum amylase (64.4%) and lipase (95.2%) were prominent diagnostic markers. Other abnormal laboratory parameters, such as elevated transaminase (90.8%) and C-reactive protein (86.4%), provided valuable insights for diagnosis and management. Conclusion: The study found acute pancreatitis with a wide range of clinical presentations and aetiologies. Abdominal pain is the most common symptom and gallstones are the most common causes. The study has evaluated the outcomes and complications of acute pancreatitis indicating that a significant proportion of cases had a favorable prognosis. A notable proportion required referral to higher levels of care, suggesting the complexity and severity of some instances of acute pancreatitis. A smaller percentage left against medical advice, and a few cases resulted in mortality. J Com Med Col Teachers’ Asso July 2023; 27(2): 67-74